Structure and function of a novel lineage-specific neutralizing epitope on H protein of canine distemper virus - Bi, Zhenwei; Wang, Wenjie; Xia, Xingxia (Frontiers in Microbiology, 2023)
Canine distemper virus (CDV) belongs to the Morbillivirus genus of the Paramyxoviridae family, which causes a threat to many animals. The hemagglutinin (H) protein, the major neutralizing target, binds to cells receptors and subsequently triggers fusion for initial viral infection. So it’s necessary to clarify the detailed neutralizing epitopes of H protein and extend the knowledge of mechanisms of virus neutralization. In this study, a neutralizing monoclonal antibody (mAb) 2D12 against CDV H protein, which had different reactivity with different CDV strains, was generated and characterized. A series of truncated H proteins were screened to define the minimal linear epitope 238DIEREFD244 recognized by 2D12. Further investigation revealed that the epitope was highly conserved in vaccine lineage of CDV strains, but two substitutions (D238Y and R241G) in the epitope appeared in most CDV strains of other lineages, causing the change of antigenicity. Thus, the epitope represents a novel lineage-specific neutralizing target on H protein of CDV for differentiation of vaccine lineage and other lineages of CDV strains. The epitope was identified to localize at the surface of H protein in two different positions in a three-dimensional (3D) structure, but not at the position of the receptor-binding site (RBS), so the mAb 2D12 that recognized the epitope did not inhibit the receptor binding of the H protein. But mAb 2D12 interfered with the H-F interaction for inhibiting membrane fusion, suggesting that this epitope plays key roles for formation of H-F protein oligomeric structure. These data will contribute to our understanding of the structure, function and antigenicity of CDV H protein and mechanisms of virus neutralization.